1973
DOI: 10.1002/bit.260150203
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental conditions on the macromolecular composition of Candida utilis

Abstract: SummaryGlucose-limited chemostat cultures of Candida utilis were cultivated at various pH levels (3.0-7.5), temperatures (15-37.5"C), dilution rates (0.06-0.42 hr-l), and with different nitrogen sources (NH4+ and NO,-). The ratio of total nucleic acid to protein increased with increase in dilution rate at constant temperature and decreased with increase in temperature at constant dilution rate. The pattern of these variations is consistent with the hypothesis that the nucleic acid to protein ratio is a functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 26 publications
5
16
0
Order By: Relevance
“…The results also show that by increasing the dilution rate, the efficiency of nucleic acid in protein synthesis (protein/nucleic acid x dilution rate) increased. A similar effect was reported by Alroy and Tannenbaum (1973) and Levine and Cooney (1973).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results also show that by increasing the dilution rate, the efficiency of nucleic acid in protein synthesis (protein/nucleic acid x dilution rate) increased. A similar effect was reported by Alroy and Tannenbaum (1973) and Levine and Cooney (1973).…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have shown that maximum growth rate, biomass yield and accumulation of storage compounds in cells are affected by the elemental composition of the medium, such as N, P, S, Ca, Mg, Fe, Cu and Zn (Duguid and Wilkinson 1953;Wilkinson et al 1954;Corpe 1964;Mateles and Battat 1974;Goldberg and Er-el 1981;Tempest and Wouters 1981 ;Banat et al 1989). In addition, varOffprint requests to: A. S. Abu-Ruwaida ious cultivation conditions such as temperature, pH, dissolved oxygen and dilution rate affect specific growth rate, biomass yield and accumulation of storage compounds (Alroy and Tannenbaum 1973;H~iggstr6m 1977;Bull and Brown 1979;Litchfield 1979;Lallai et al 1988). …”
Section: Introductionmentioning
confidence: 99%
“…Protein content of the yeast yields were similar to earlier published values given by Forage (1978) and Rale (1984), and the total nucleic acid concentration of 8.1% is comparable with the figure given by Alroy & Tannenbaum (1973) for C utilis grown in synthetic medium. Amino acid concentrations in the yeasts also compared favourably with F.A.O.…”
Section: Discussionsupporting
confidence: 69%
“…The protein content decreased markedly at higher growth rates, coinciding with an increase in total carbohydrates. Whilst there is little published information on changes in the carbohydrate content of C. utilis, several authors have examined the variation in protein content with growth rate (Brown & Rose, 1969;Alroy & Tannenbaum, 1973;Herbert, 1976). Most of these reports have shown a pattern fairly consistent with Herbert's original work on Aerobacter (Herbert,196 l), where protein content varied only slightly with dilution rate, in marked contrast to the present results.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…Previous reports have described the growth of Candida utilis in carbon-limited chemostat conditions, mainly in connection with an evaluation of the potential of this yeast for single-cell protein production (Brown & Rose, 1969;Alroy & Tannenbaum, 1973;Herbert, 1976). The effect of growth rate on macromolecular composition has received considerable attention in these studies; the wide variations in composition which have been observed appear to be related to the complex or incomplete growth media employed in most experiments reported.…”
Section: Introductionmentioning
confidence: 99%